2011
DOI: 10.1136/sti.2010.048017
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus vaccine and behavioural disinhibition

Abstract: Objectives We sought to identify characteristics of parents who believe in sexual disinhibition and that Pap smears can safely be stopped after females receive HPV vaccine. Methods We surveyed 647 parents of adolescent girls living in areas of North Carolina with elevated rates of cervical cancer. We report data primarily from a survey conducted in Fall 2008. Results Only 16% (101/647) of parents agreed that teenage girls who receive HPV vaccine may be more likely to have sex. Parents who believed in vacci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
35
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 32 publications
1
35
0
Order By: Relevance
“…This study provides a clinical validation and extends our understanding of numerous surveys reporting that most young women did not plan to modify their sexual behaviors after HPV vaccination. 15,[19][20][21][22][23][24][25] Although most previous surveys have been cross-sectional, a recent longitudinal survey conducted in the United Kingdom documented no difference in the proportion of women reporting initiation of sexual activity after HPV vaccination 30 ; however, that study was conducted in women aged 16 to 18, of whom 37% had already become sexually active. 30 In our analysis, HPV vaccination at ages 11 through 12 did not increase the likelihood of seeking medical attention for outcomes related to sexual activity with up to 3 years of follow-up.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…This study provides a clinical validation and extends our understanding of numerous surveys reporting that most young women did not plan to modify their sexual behaviors after HPV vaccination. 15,[19][20][21][22][23][24][25] Although most previous surveys have been cross-sectional, a recent longitudinal survey conducted in the United Kingdom documented no difference in the proportion of women reporting initiation of sexual activity after HPV vaccination 30 ; however, that study was conducted in women aged 16 to 18, of whom 37% had already become sexually active. 30 In our analysis, HPV vaccination at ages 11 through 12 did not increase the likelihood of seeking medical attention for outcomes related to sexual activity with up to 3 years of follow-up.…”
Section: Discussionmentioning
confidence: 66%
“…[13][14][15][16][17][18] Most teenage girls surveyed on knowledge, attitudes, and practices related to HPV vaccination reported they would not modify their sexual behaviors after HPV vaccination. 15,[19][20][21][22][23][24][25] Most of these studies were limited by the use of selfreported, cross-sectional surveys, 15,[19][20][21][22][23][24][25] however, and it is unknown if these survey results would directly translate to clinical outcomes.…”
mentioning
confidence: 99%
“…This finding is consistent with a past study that found that conservative political beliefs were associated with greater concern about sexual disinhibition occurring among adolescent girls who receive HPV vaccine. 14 Because parent age was not associated with beliefs in sexual disinhibition, our hypothesis that older parents would express stronger beliefs in sexual disinhibition was not supported. Past studies have found a null or positive association between parent age and endorsement of sexual disinhibition beliefs.…”
Section: Discussionmentioning
confidence: 87%
“…The present study uses data from a national sample of parents and their adolescent sons to determine the prevalence of this belief and identify correlates of having this belief. Based on our previous research among parents of adolescent girls, 14 we hypothesized that parents who were younger and more liberal in their political views would have weaker beliefs in sexual disinhibition occurring among boys who receive HPV vaccine. We also hypothesized that sons with higher knowledge about HPV would be less likely to agree with the notion that HPV vaccine may cause sexual disinhibition.…”
mentioning
confidence: 99%
“…More systematic evidence for such beliefs among religious conservatives is offered by Schuler et al (2011). raises concerns about selection bias and spurious causality: because these girls were not randomly assigned to treatment and control groups, but rather selfselected (i.e., parent-selected) into the HPV vaccination treatment, it is harder to draw inferences about the causal relationship between vaccination and sexual activity. For example, it could be the case that the parents who chose vaccination for their preteen girls were also more likely to educate their girls about the health risks of sex and the advantages of postponing sexual activity; if so, this may have masked any disinhibiting effects of the vaccination itself.…”
mentioning
confidence: 99%